Ecopoeticidades exodais no Canto de Moisés: um estudo bíblico-teológico de Ex 15,1-18 - Barros, Paulo Freitas (2023)
This doctoral thesis presents an exegetical and/or biblical-theological study of the Song of Moses (Ex 15:1-18), a lyrical poem originally composed in ancient Hebrew. It is the first song to be sung in the Hebrew Bible, like the Psalms and other songs present in the various books belonging to this millennial artwork of literature. Written in verses and/or lines, the Song of Moses apparently consists of eleven short stanzas, each of which extends to one, two or, at most, three verses. The study of each literary unit, including the narrative insertion of the song in the book of Exodus (Ex 15:1a-b), begins with the translation of the biblical text into Portuguese and the investigation of its poetic configuration. In this way, the rhythm and melody of the poem are discovered. Next, the theme or subject matter developed in each stanza of the poem is addressed. In this way, the content, or the question of what the lyrics of the Song of Moses say prevails. Along with this second concern, it is observed that ecopoeticities bring a unique contribution to the poem studied here. In this case, on the one hand, the geographical space of the sea is targeted (Ex 15:1c-11). On the other hand, the land (Ex 15:12-18) gains attention. This bipolarity, favored by the Song of Moses itself, gives rise to the subdivision of the present research into two parts. In addition, it is noticeable that the poem investigated here sometimes welcomes abiotic beings – air, water, soil and heat – and sometimes some plants and animals, non-human beings that are part of the geographical spaces focused on. Finally, the newness of this Doctoral Thesis is born, above all, from the attempt to carry out a green reading of the Song of Moses in Ex 15:1-18. In this way, the research undertaken here aims to contribute to what has become increasingly important in the world of biblical studies in the last two to three decades: the realization that the texts of Sacred Scripture do not only think of God and human beings, but also of non-human beings. In this way, the Bible resists theocentrism and/or anthropocentrism, adding its religious and/or theological ecopoeticities to the urgent search for a renewed understanding of the socio-environmental dimensions belonging to today's world